Simulation and experimental research on subsurface damage of silicon nitride grinding. Issue 7 (May 2018) - Wan, Linlin; Liu, Zhijian; Deng, Zhaohui; Li, Le; Liu, Wei
Abstract: A finite element model of silicon nitride grinding was created based on virtual abrasives with a truncated polyhedral shape, to simulate the subsurface damage depth. Due to the influence of materials on light reflection, a new method to detect the subsurface damage depth was presented based on the light intensity. A series of orthogonal experiments were accomplished by using a MGK7120 × 6/F NC surface grinder. The influence of the grinding parameters, such as the wheel speed, workpiece speed and grinding depth, were analysed for their effects on the subsurface damage depth. A prediction model of the subsurface damage depth was built by conducting a regression analysis of the experimental data. The results indicated that the average error between the model prediction and experimental testing was approximately 9%, which validated the predication accuracy and the generalization ability of the prediction model.